2001
DOI: 10.1136/heart.85.4.458
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk for ischaemic events is related to combined RAS polymorphism

Abstract: Objective-To determine whether the angiotensin converting enzyme (ACE) and the angiotensin II type 1 receptor (AT 1 R A1166C) gene polymorphism interact to increase the risk of ischaemic events, and whether this can be explained by the progression of angiographically defined coronary atherosclerosis. Design-Prospective defined substudy of the lipid lowering regression trial (REGRESS). Setting-University hospital. Patients-885 male patients with stable coronary artery disease. Main outcome measures-Incidence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 26 publications
(22 reference statements)
0
17
0
2
Order By: Relevance
“…Ludwig et al [16] and Fomicheva et al [17] observed a significant interaction between the AGT and ACE genes. Tiret et al [33] and van Geel et al [34] found a significant association between ACE and AGTR1, and Á lvarez et al [35] have demonstrated an interaction between AGT and AGTR1. These results strengthen the hypothesis that genotypic combinations are more important than single gene polymorphism alone.…”
Section: Discussionmentioning
confidence: 96%
“…Ludwig et al [16] and Fomicheva et al [17] observed a significant interaction between the AGT and ACE genes. Tiret et al [33] and van Geel et al [34] found a significant association between ACE and AGTR1, and Á lvarez et al [35] have demonstrated an interaction between AGT and AGTR1. These results strengthen the hypothesis that genotypic combinations are more important than single gene polymorphism alone.…”
Section: Discussionmentioning
confidence: 96%
“…22 Similarly, AT1R A1166C reportedly correlates with CVD, including increased left ventricular mass index 16 and diabetic nephropathy. 32 Previous cohort studies have also shown that AT1R A1166C significantly correlates with the frequency of restenosis following coronary artery angioplasty, 33 incidence of CVD and mortality, 34 and myocardial infarction. 35 Several studies have indicated that these polymorphisms significantly correlated with CVD or prognosis; however, little is known about how RAS gene polymorphisms affect the onset of CVD or prognosis in clinical setting.…”
Section: Visit-to-visit Blood Pressure Variability and Ras Gene Polymmentioning
confidence: 95%
“…A meta-analysis of 46 studies including a total of 32,715 Caucasian subjects concluded that the insertiondeletion polymorphism in ACE gene was not associated with increased risk of MI, CAD, or ischemic cerebrovascular disease (Agerholm-Larsen et al 2000). It has been suggested that a combination of genotype variants of the renin-angiotensin system genes could be a signiWcant determinant of ischemic events (van Geel et al 2001) and CAD (Kretowski et al 2007).…”
Section: Other Genes Modulating Susceptibilty To Atherosclerosismentioning
confidence: 99%